The Classroom teacher's guide to instructional and curricular modifications [videorecording].1, modifications 101 making the curriculum accessible to all students. - Dover, Wendy Fetner (Master Teacher, 2006)
Provides a framework for teachers to work through the barrier issues of modification, suggests ways to share information while respecting confidentiality, and gives ways to approach assessment accommodations and modifications.